Wind Energy Research and Development Denter in Sidenreng Rappang Regency - Hadrianti; Nurhayati Kamaruddin; Izharul Haq (Universitas Ichsan Sidenreng Rappang, 2026)
The Indonesian government prioritizes Wind Power Plants (PLTB) within the national energy mix, positioning Sidenreng Rappang (Sidrap) Regency as a strategic pilot location with the operation of the 75 MW Sidrap PLTB. However, current research on wind energy remains heavily dominated by climatological and technical aspects. This creates a significant gap due to the absence of a physical facility that integrates social dimensions, innovation governance, and environmental risk mitigation, such as addressing local high-wind phenomena. This study aims to design a Wind Energy Research and Development Center facility in Watang Pulu District, Sidrap Regency. The design method employs a Glass-Box approach that is systematic, transparent, and data-driven. The functional design concepts of the building are integrated through the application of Bioclimatic Architecture, which is responsive to the tropical climate and adapts the local wisdom of traditional Bugis Stilt House architecture. The design results demonstrate an axial-patterned site layout that measurably segregates public, semi-public, and private zones to reduce noise pollution from the main road. The main mass configuration is aerodynamically developed into a curved geometry (oval/C-shape) to minimize wind resistance, deflect solar radiation via a secondary skin, and optimize vertical-horizontal cross-ventilation through an elevated building structure (stilt understructure). This facility is equipped with modular aerodynamics laboratories, a field turbine testing area, and a public educational gallery. The design of this research center successfully synergizes renewable energy technology with contextual-bioclimatic architecture. This facility serves as an energy-independent, adaptive, and sustainable research infrastructure solution capable of strengthening cultural identity and local public energy literacy